Management of post-operative delirium following stereoelectroencephalography electrode placement for drug resistant epilepsy: Lessons learned from two case reports - Katherine Belanger; Fabio Grassia; Michael W. Kortz; John A. Thompson; Sam DeStefano; Steven Ojemann (Epilepsy & Behavior Reports, 2021)
Post-operative delirium (POD) represents a unique challenge in the care of any surgical patient but is especially challenging in neurosurgical inpatient management due to a host of potentially significant predisposing factors. Patients undergoing stereoencephalography (SEEG) for diagnosis of drug resistant epilepsy are at unique risk due to safety concerns, yet POD has been underdiscussed in this population. Patients should be counseled pre-operatively about their risk and subsequent steps be taken post-operatively. We present two cases of POD status-post SEEG and propose a mechanism by which future post-operative care be coordinated by the physician, patient, and patient’s family.